Estresse salino em plantas jovens de cana-deaçúcar: respostas bioquímicas e fisiológicas - Chiconato, Denise Aparecida [UNESP] (2016)
Sugarcane is a globally important crop. Brazil is the largest producer of sugarcane and stands out in the marketing and exportation of sugar and ethanol derived from this culture. The various abiotic stresses adversely change plant growth and between the stresses, soil salinity is presented by the severe reduction in productivity, it is the main stressor in arid and semi-arid climates. This study aimed to verify the effects of NaCl on the development of sugarcane young plants, SP 81- 3250 and IAC 87-3396 cultivars, through the study of physiological-biochemical variables: (I) the osmoprotectors proline, glycine betaine and sucrose, (II) the occurrence of nutritional changes the ratio Na+/K+ (III) lipid peroxidation (IV) effect of NaCl in the activity of nitrate reductase enzyme; (V) the effect of salt stress on gas exchange; (VI) the growth of shoots and roots of the sugarcane cultivars under salt stress. Thus, it was used four concentrations of NaCl (0, 40, 80 and 160 mM) and made the following assessments: Na+ and K+ accumulation in the leaves and roots, compatible osmolytes: proline, glycine betaine and sucrose, water potential, peroxidation lipid, activity of nitrate reductase enzyme, gas exchange, total chlorophyll, quantum yield of PSII and shoot and root growth at 15 and 30 days of development after stress application. The results showed higher susceptibility of the cv. IAC 87-3396 by higher accumulation of Na+ and Na+/K+ ratio, increase in lipid peroxidation by MDA accumulation and greater negative effect on gas exchange. Both cultivars showed proline accumulation under stress, however, the cv. SP 81- 3250 showed in addition faster accumulation of this amino acid, reduced lipid peroxidation and higher growth. Under severe salt stress cv. IAC 87-3396 is more susceptible.